A PFC-based PMBLDCM drive for air-conditioner using half-bridge buck converter. (1st January 2012) - Singh, Sanjeev; Singh, Bhim
A diode bridge fed buck half-bridge DC-DC converter fed from single-phase AC mains is used as a single-stage power factor correction (PFC) converter for feeding a voltage source inverter (VSI) based permanent magnet brushless DC motor (PMBLDCM) drive. The PMBLDCM is used to drive a compressor load of an air conditioner through a three-phase VSI fed from a constant DC voltage. The speed of the compressor is controlled using simple proportional and integral (PI) controller. The proposed PFC converter-based PMBLDCM drive is designed, modelled and its performance is simulated in MATLAB-Simulink environment for an air conditioner driven through a 1.5 kW, 1, 500 rpm PMBLDCM. Simulated results of the proposed drive are presented to demonstrate its improved performance with PFC feature in wide range of speed and an input AC voltage.